Geometry of design a workbook - Kim, Nam-Ho; Kumar, Ashok V.; Snider, Harold F. (Waltham, MA Woodhead Publishing, 2015)
Engineering drawing is the "instrument of communication" upon which the designer must place all information necessary to define a new product. Computer-aided design (CAD) courses often involve teaching solid modelling software, and we view CAD as an engineering communication tool for manufacturing. As the technology of engineering design is in transition from paper drawings to solid models, its education must address the challenge of covering both technologies. Geometry of design integrates drafting technology based on experience with engineering design education. This workbook has evolved from the course “Computer-Aided Graphics and Design” at the University of Florida, and many pages of this textbook can be used for student assignments. In order to help students to familiarize themselves with the manufacturing field experience, most assignments are to be submitted in the form of complete working drawings of the parts and assembly. The first three chapters introduce basic engineering drawing definitions and practices. The following four chapters cover design and descriptive geometry, and subsequent chapters move on to dimensions, assembly line design and surface development.--Provided by publisher.
Electronic reproduction.
Keywords: Computer-aided design; Electronic books